Anemia in hemodialysis patients, experience from a tertiary care hospital - Sabir, Omer; Riaz, Muhammad Mohsin; Qadri, Ghulam Abbas; Parviz, Raheel; Azhar, Ayesha; Usman, Muhammad; Asif, Muhammad; Tarif, Nauman (Pakistan Journal of Kidney Diseases, 2021)
Anemia in hemodialysis population is common and requires constant vigilance by treating nephrologist and the dialysis room personnel. Anemia is associated with reduced quality of life, increased risk of CVD, hospitalization, and even mortality1. Materials and Methods: This was a cross sectional analysis of prevalent hemodialysis patients aged 18 – 80 years at Fatima Memorial Hospital. Anemia was defined as a hemoglobin concentration of less than 10 mg/dL. RESULTS Total number of participants was 36. The mean age was 48.56 + 19.15 years. There were 27 (75%) males. 53.3% patients were found to be anemic. CONCLUSIONS In this study, almost half of the patient population was anemic. This strongly suggests that